2016
DOI: 10.1007/s00453-016-0252-6
|View full text |Cite
|
Sign up to set email alerts
|

Matchings with Lower Quotas: Algorithms and Complexity

Abstract: We study a natural generalization of the maximum weight many-to-one matching problem. We are given an undirected bipartite graph G = (A∪ P, E) with weights on the edges in E, and with lower and upper quotas on the vertices in P.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(49 citation statements)
references
References 36 publications
0
49
0
Order By: Relevance
“…The only exception is the combination (stable)-greedy max that exhibits highly varying running times, reaching 5157 seconds for the instance of 2015. 4 • Comparing the combinations (minimax)- * and (stable+minimax)- * we observe that some stability is lost if only the minimax constraint is included. On the other hand, looking at the column "Utility", which gives the deviation from the best utility, we see instead that the loss in global utility is very small if also stability is included among the constraints.…”
Section: Combinations Of Criteriamentioning
confidence: 93%
See 1 more Smart Citation
“…The only exception is the combination (stable)-greedy max that exhibits highly varying running times, reaching 5157 seconds for the instance of 2015. 4 • Comparing the combinations (minimax)- * and (stable+minimax)- * we observe that some stability is lost if only the minimax constraint is included. On the other hand, looking at the column "Utility", which gives the deviation from the best utility, we see instead that the loss in global utility is very small if also stability is included among the constraints.…”
Section: Combinations Of Criteriamentioning
confidence: 93%
“…Consequently, they conclude that the matching problem is NP-complete, already when all vertices in U have size 1 or 2 and each vertex in V has capacity 2. Arulselvan et al [4] have recently shown that the existence problem remains NP-complete even without group registrations but with lower bounds on the number of students per team and with closed teams allowed. More precisely, they have shown that the optimization problem asking to maximize the total weight of the assignment can be solved efficiently if the number of applicant students for every team is at most 2 while it becomes NP-hard as soon as there are teams with at least 3 applicant students and students with preference lists of at least 2 projects or, alternatively, as soon as there are projects with upper bound of at least 3.…”
Section: Problem Definitionmentioning
confidence: 99%
“…Our work also fits into the line of research that addresses computationally hard problems in the area of stable matchings by focusing on instances with bounded preference lists [6,27,29,32,41] or by applying the more flexible approach of parameterized complexity [1,3,5,37,38].…”
Section: Related Workmentioning
confidence: 99%
“…There is a natural Turing reduction from SMC to the variant considered by Knuth. Coarse analysis into polynomial-time solvable and NP-hard cases has been studied by several researchers [1].…”
Section: Introductionmentioning
confidence: 99%
“…Related Works Recently, the study of matching models with lower quotas has developed substantially [1,7,13,15,16,18,21,22]. The Hospitals/Residents problem with lower quotas (HR-LQ) was first studied by Hamada et al [15,16], who considered the minimization of the number of blocking pairs subject to upper and lower quotas.…”
Section: Introductionmentioning
confidence: 99%